Effect of curing methods on the strength of interlocking paving blocks. Issue 1 (1st January 2020) - Atoyebi, O. D.; Ikubanni, P. P.; Adesina, A.; Araoye, O. V.; Davies, I. E. E.
Abstract: Interlocking paving blocks (IPB) are an integral part of the pavement infrastructure in developing countries. However, the effect of curing methods on the performance of IPB is vague, and the understanding of this phenomenon will ensure optimum strength and performance for subsequent IPB to be produced. Therefore, this study was carried out to investigate the effect of different curing methods on the compressive strength of IPB. The curing methods evaluated are hot water, open-air, ponding, membrane, earthing and sprinkling methods. Dog-bone samples with a cross-sectional area of 24, 401 mm 2 were designed and made. The samples are cured using different methods and tested at 7, 14, 21, 28 and 56 days except for those cured in hot water which are tested at 3, 6, 9, 24 and 48 hours after casting. Results from this study indicate that the curing method strongly affects the compressive strength of the IPB. The optimum curing method was found to be the ponding method as it resulted in the highest compressive strength.